Rancang Bangun Sistem Pelayanan Kesehatan di Klinik Pratama Berbasis Web (Programmer) - Alzikri; Novi Yona Sidratul Munti; Emon Azriadi (PT Pustaka Cendekia Group, 2025)
The advancement of technology has provided convenience in various aspects of life, including medical record administration in clinics. The internet has become a primary necessity that supports web-based information systems to improve the efficiency and effectiveness of healthcare services. In line with this, Klinik Pratama Universitas Pahlawan Tuanku Tambusai faces challenges in patient registration and administrative processes, which are still manually conducted using Excel and paper. To address this issue, a web-based administrative system is needed to optimize human resources, accelerate workflow, and enhance accuracy and patient services. The system is also developed using the Laravel framework. The implementation of this system can improve data recording and management more effectively and efficiently, thereby supporting better healthcare service quality.